KNOWLEDGE OF DIAGNOSIS, TREATMENT AND LATE EFFECTS IN ADOLESCENT AND YOUNG ADULT SURVIVORS OF CHILDHOOD AND ADOLESCENT CANCER - Syed, Iqra A. (My University, 2013)
Abstract
Purpose: While most children diagnosed with cancer survive their initial disease, the intensive treatments they receive place them at risk for late effects. Long-term follow-up (LTFU) care is recommended for cancer survivors for surveillance and early detection of late effects. Knowledge, or lack thereof, regarding diagnosis, treatment and late effects is an important barrier and/or facilitator for attending LTFU care in adolescent and young adult (AYA) cancer survivors. The purpose of our study was to examine the extent of knowledge in Canadian AYA survivors of childhood and adolescent cancer, and identify factors associated with such knowledge.
Methods: Survivors of childhood and adolescent cancer, between the ages of 15 and 26 years, were recruited from three pediatric oncology centres. Patients were invited to participate in the study through mail and clinic recruitment. A questionnaire booklet, including the Cancer Knowledge Survey that asked questions about cancer, treatment and late effects, was administered to collect necessary information. Clinical data was extracted from hospital records to validate participants’ answers.
Results: 250 (response rate= 75.5 percent) out of 331 patients invited to participate completed the questionnaire booklet. 18 (7.2 percent) participants lacked information regarding their type of cancer, whereas 25 (10.3 percent) participants were ‘not knowledgeable’ of their treatment. Lack of knowledge regarding treatment was associated with being non-white [odds ratio= 0.3 (0.2-0.6)] compared with white. Also, 83 (33.5 percent) participants were unaware of their late effects. Lack of knowledge regarding late effects was associated with younger age [odds ratio= 1.2 (1.1-1.3)], and having leukemia compared with embryonal tumour [odds ratio= 3.41 (1.10-10.6)].
Conclusion: Results from this study highlights important knowledge deficits, especially in terms of understanding risk of late effects from cancer treatments. Findings from this study can be used to design programs and interventions aimed at increasing cancer knowledge in AYA cancer survivors.
Keywords: cancer; neoplasm; knowledge; Adolescent and young adult; survivor; Oncology; Oncology